No place like home – Or is there? Extended transformational potential of nursing homes during vital conjunctures - Leino Henna M.; Hurmerinta Leila; Sandberg Birgitta; Menzfeld Mira (Wiley, 2022)
Aims and objectives
The purpose of this study is to explore how the concept of ‘feeling at home’ manifests in nursing home environments and influences the transformational potential of such homes—servicescapes where customers experience vital conjunctures.
Background
Recent research on places highlights the potential of service venues as places that can promote well-being. Nursing homes bridge the concepts of ‘home’ and a service with transformational aspirations. Moving to a nursing home can be regarded as a vital conjuncture, yet despite the resultant mixed emotions, nursing homes can generate positive changes and meaningful relations.
Design; Methods
A qualitative field study with ethnographic features was conducted in two Finnish nursing homes. The data consist of observations and 64 semi-structured interviews. COREQ guidelines were followed.
Results
‘Feeling at home’ is built on: (1) artefacts and surroundings, (2) functions and activities and (3) relationality and atmosphere. A home-like experience related to each category is important in enabling customers to feel at home, thus assisting in dealing with the vital conjuncture, but the transformative power of nursing homes is linked most closely to respectful, kind attendance of the others and a positive atmosphere.
Conclusions
The roles of nurses and a homely servicescape are essential in dealing with residents' vital conjunctures, whether those residents employ resistance or adjustment coping methods. Positive transformations that evoke residents' re-balancing and well-being are enabled in nursing homes that support residents' important relationships, identity, safety and self-efficacy. This positive transformation also aids family members with their associated vital conjunctures, thus multiplying the service's transformational potential.
Patient or public contribution
Service users and caregivers were involved in the design and conduct of the data in this study.
Relevance to clinical practice
Creating a homely atmosphere in nursing homes fosters not only residents' but also family members' re-balancing and well-being.